Records Of The Colony Of New Plymouth In New England 66 (1861) - (:unkn) unknown (My University, 1656)
Laws of Plymouth Colony (1656). And likewise that no Indian shall discharge any gun on the Lords day at any thing to the breach of the Sabbath and disturbance of the English; as they will answer it at their peril.
Keywords: DISCHARGE; ENSLAVED PERSONS & OTHER MINORITIES